2020
DOI: 10.1007/s40273-020-00893-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the EQ-5D-3L and EQ-5D-5L

Abstract: Introduction The EQ-5D-3L (3L) and EQ-5D-5L (5L) are both frequently used measures of health status. Previous studies have found the EQ-5D-5L to have superior measurement properties but no study has compared the two measures in a large general population survey using matched respondents. Methods Using data from the GP Patient Survey, coarsened exact matching was used to match individuals completing the 3L in 2011 with those completing the 5L in 2012. Measurement properties were assessed for a general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 27 publications
9
51
1
1
Order By: Relevance
“…Consistent with most other studies [16,41,42] including an assessment of the subgroup of multimorbid patients in a study by Thompson et al [11], in our sample we observed a reduction in ceiling effects from using the EQ-5D-5L (22%) compared to the EQ-5D-3L (29%). The EQ-5D-5L therefore appears to better capture variability in health status among those who have a high level of health, compared with the EQ-5D-3L.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with most other studies [16,41,42] including an assessment of the subgroup of multimorbid patients in a study by Thompson et al [11], in our sample we observed a reduction in ceiling effects from using the EQ-5D-5L (22%) compared to the EQ-5D-3L (29%). The EQ-5D-5L therefore appears to better capture variability in health status among those who have a high level of health, compared with the EQ-5D-3L.…”
Section: Discussionsupporting
confidence: 92%
“…Also consistent with all the studies identified in a systematic review by Buchholz et al in 2018 [16] was our finding of an overall improvement in informativity from using the 5L compared to the 3L. This was the consequence of a substantially higher Shannon evenness index score for the mobility item of the 5L compared with the 3L; which was also observed in a study of multimorbid adults by Thompson et al [11]. However, informativity in our study was higher on the 3L than with the 5L for self-care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The recently published study by Thompson et al is also a kind of "indirect study". Still, authors used the matching method to join individuals completing the EQ-5D-3L with those completing the EQ-5D-5L, and thus increasing the sample size [70].…”
Section: Discussionmentioning
confidence: 99%
“…However, each dimension of EQ-5D-5L has 5 response categories: 1) no problem; 2) slight problems; 3) moderate problems; 4) severe problems; and 5) extreme problems. Previous studies found that EQ-5D-5L have superior measurement properties than EQ-5D-3L [32][33][34][35]. The value set of EQ-5D-5L was developed based on standardized valuation study protocol (EQ-VT) developed by the EuroQol Group [36].…”
Section: Eq-5d-5lmentioning
confidence: 99%